Changing tectonic controls on the long‐term carbon cycle from Mesozoic to present. (17th December 2014) - Mills, Benjamin; Daines, Stuart J.; Lenton, Timothy M.
Abstract Tectonic drivers of degassing and weathering processes are key long‐term controls on atmospheric CO2. However, there is considerable debate over the changing relative importance of different carbon sources and sinks. Existing geochemical models have tended to rely on indirect methods to derive tectonic drivers, such as inversion of the seawater 87Sr/86Sr curve to estimate uplift or continental basalt area. Here we use improving geologic data to update the representation of tectonic drivers in the COPSE biogeochemical model. The resulting model distinguishes CO2 sinks from terrestrial granite weathering, total basalt weathering, and seafloor alteration. It also distinguishes CO2 sources from subduction zone metamorphism and from igneous intrusions. We reconstruct terrestrial basaltic area from data on the extent of large igneous provinces and use their volume to estimate their contribution to degassing. We adopt a recently published reconstruction of subduction‐related degassing, and relate seafloor weathering to ocean crust creation rate. Revised degassing alone tends to produce unrealistically high CO2, but this is counteracted by the inclusion of seafloor alteration and global basalt weathering, producing a good overall fit to Mesozoic‐Cenozoic proxy CO2 estimates and a good fit to 87Sr/86Sr data. The model predicts that seafloor alteration and terrestrial weathering made similar contributions to CO2 removal through the Triassic and Jurassic, after which terrestrial weathering increased and seafloor weathering declined. We predict that basalts made a greater contribution to silicate weathering than granites through the Mesozoic, before the contribution of basalt weathering declined over the Cenozoic due to decreasing global basaltic area.